The odds of even getting home early ; Railroading at the LRT ; Going places [videorecording] - Garcia, Carol; Lazaro, Cheche; Nakpil, Henry; Valdellon, Nessa (The Probe Team, 1995)
Metro-Manilans are caught in a spirit of debate on a better traffic scheme, color coding or odd-even scheme in solving traffic problems. Investigates the controversy on graft and corruption in LRT's construction project. A look at transport alternatives like solo taxi (motorcycle) ; trolley and helicopter.